2014
DOI: 10.1039/c3ra47755j
|View full text |Cite
|
Sign up to set email alerts
|

Sequential recognition of zinc ion and hydrogen sulfide by a new quinoline derivative with logic gate behavior

Abstract: A Schiff base-type fluorescent chemosensor L has been synthesized for Zn2+ detection, and the consequent product of L and Zn2+, L–2Zn, is an excellent indicator for H2S for displacement of Zn2+ from the complex L–2Zn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…However, the addition of H 2 PO 4 À ions extracted the Zn 2 + ion from the 45-Zn 2 + complex which resulted into free 45 and generate yellow fluorescence. Dong et al [147] have reported a multi responsive and selective sensor 46 as a probe to monitor Zn 2 + and for the sequential detection of H 2 S (Scheme 48). The receptor showed high sensitivity and selectivity for Zn 2 + detection with a detection limitof 10 À7 M. The fluorescence intensity of compound 46 can be recovered by adding HS À to the Zn 2 + sensing system via the Zn 2 + displacement approach.…”
Section: Detection Of Pyrophosphates and H 2 Pomentioning
confidence: 99%
See 1 more Smart Citation
“…However, the addition of H 2 PO 4 À ions extracted the Zn 2 + ion from the 45-Zn 2 + complex which resulted into free 45 and generate yellow fluorescence. Dong et al [147] have reported a multi responsive and selective sensor 46 as a probe to monitor Zn 2 + and for the sequential detection of H 2 S (Scheme 48). The receptor showed high sensitivity and selectivity for Zn 2 + detection with a detection limitof 10 À7 M. The fluorescence intensity of compound 46 can be recovered by adding HS À to the Zn 2 + sensing system via the Zn 2 + displacement approach.…”
Section: Detection Of Pyrophosphates and H 2 Pomentioning
confidence: 99%
“…Dong et al . have reported a multi responsive and selective sensor 46 as a probe to monitor Zn 2+ and for the sequential detection of H 2 S ( Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Intrigued by relay recognition of metal ions and anions [13][14][15], we hope a new ratiometric response for citrate could be established through metal ions displacement approach. Based on the strategy, a ratiometric sensor for a metal ion is necessary, and then the metal ion bonded with the sensor can be exactly captured by citrate while a reverse spectrum change appears.…”
Section: Introductionmentioning
confidence: 99%
“…Among various detection methods, optical detection methods (via fluorescence or colorimetric changes) are the most promising detection techniques owing to their low cost, simplicity, low detection limit and useful application in environmental, biological, and industrial areas [23][24][25][26][27][28][29][30][31]. For the determination of Cu 2+ , most of previous works have reported the "on-off" fluorescence sensors [32][33][34].…”
Section: Introductionmentioning
confidence: 99%